Variabel Daya Tanggap dan Empati Mempengaruhi Kepuasan Pasien Rawat Jalan pada RSUD H. Abdurrahman Sayoeti Kota Jambi - Ahmad Tarmizi; Denny Asmas; Putri Yasmin (Universitas Batanghari Jambi, 2023)
The main problem is also divided into severalsub-problems or exploration questions about service, videlicet 1) What are the service quality variables conforming of power variables? responsiveness, empathy, and patient satisfaction affect sanitarium case satisfaction. H. Abdurrahman Sayoeti Jambi City, and 2) Which service quality variable has the most dominant effect on patient satisfaction at the Sanitarium. The H. Abdurrahman Sayoeti Regional General Hospital, Jambi City, is a Type D General Hospital belonging to the Regional Government of Jambi City. This sanitarium is located at Jl.K.H Hasan AnangNo. 33Rt. 08 Ex. Olak Kemang Kec. Jambi City Bay Lake. Grounded on Mayor RegulationNo. 42 of 2017 the Jambi City Hospital officially uses the name H. Abdurrahman Sayoeti Hospital, Jambi City. This sanitarium was preliminarily the Olak Kemang Inpatient Health Center which in 2018 was converted into a sanitarium. Responsiveness and empathy variables show a tcount value lesser than table (1,663 and 5,329) or sig> a (0.000 <0.05) therefore H0 is rejected and H1 is accepted, meaning that there's a significant positive effect between responsiveness and empathy on patient satisfaction walk in H. Abdurrahman Sayoeti Hospital, Jambi City.Â The results of this study indicate that the quality of service conforming of responsiveness ( X1) and empathy ( X2) variables has a significant effect on patient satisfaction. Experimenters' suggestions for RSUD. H. Abdurrahman Sayoeti, Jambi City, should be a hospital nurse H. Abdurrahman Sayoeti Jambi City can maximize services according to the promised time, increase trust and responsiveness to patient complaints, maintain empathy and pay attention to the physical installations of the Sanitarium H. Abdurrahman Sayoeti Jambi City.